The Relationship Between Exclusive Breastfeeding History to Stunting Incidence in Children Aged 6-24 Months in The Working Area of The Gunung Anyar Community Health Center, Surabaya, Indonesia - elisia, latiful; Etika, Risa; Aprilawati, Dwi; Mahiroh, Hodimatum (Journal of Community Medicine and Public Health Research, 2023)
Stunting is a linear growth disorder caused by malnutrition from chronic nutrient intake or recurrent chronic infectious diseases, shown by the standard deviation value (SD) unit z (Z-Score) height according to age: < -2 SD â‰¥ -3 SD. A quantitative cross-sectional design was used for this study. All mothers who visited posyandu in the vicinity of the Gunung Anyar Health Centre, Surabaya, Indonesia with infants aged 6 to 24 months comprised the study sample. Non-probability sampling was done using sequential sampling as the sampling technique. Cut-off points for univariate data analysis were used. Stunting and exclusive breastfeeding had an association with p=0.000. Stunting was significantly affected by exclusive breastfeeding. According to these findings, there was a lower incidence of stunting in children who were exclusively breastfed (2.0%) than in children who were not exclusively breastfed (30.6%). Babies who were not stunted are more prevalent (53.1%) than babies who were stunted (14.3%) for exclusive breastfeeding in the good category. In conclusion, exclusively breastfed children aged 6 to 24 months in Gunung Anyar Health Center scored well in good category. Exclusive breasfeeding has a significant impact on the incidence of stunting.